Plagiarism in Contemporary Literary Research: A Case of Academic Articles - Abbas Vaezzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Plagiarism is one of the most unethical research damage that is nowadays growing in our academic research. The purpose of this article is to examine various aspects of plagiarism in academic articles as the most prominent representative of academic studies, and in particular the academic articles of the Persian literature field. For this purpose, plagiarism is firstly defined by mentioning some examples of it in the academic articles of Persian literature. Moreover, in the future, the authorities, factors, and motives behind the plagiarism of research articles are investigated. Finally, strategies for the prevention of plagiarism and retraction of pirated articles in journals of the Persian literature field are offered. This article focuses on the inhibiting role of "plagiarism checker software" (in pre-publication), "review articles" by researchers and experts to study history (perspicacious eyes) is written in different fields of study and the publication of these articles by academic journals, retraction of stuffed articles and the cancellation of their score, as practical solutions in this regard stresses.